Kinerja Layanan dan Kepuasan Penumpang PO Arimbi Rute Jakarta – Bandung - Raka Surya Pradana; Risky Wahyudi; Dwi Endrik Setiawan (Journal of Innovative and Creativity, 2025)
This study aims to evaluate the operational performance and passenger satisfaction of PO Arimbi Bus on the Jakarta–Bandung route. Primary data were collected through questionnaires from 100 respondents at Kalideres Terminal, while secondary data were obtained from Arimbi Bus management. The analysis method used is Importance Performance Analysis (IPA) with the help of Microsoft Excel and SPSS 22.0. The results show a route performance value of 19, which is classified as good, but passenger satisfaction is slightly below expectations with a conformity score of 96.7%. Overall, Arimbi Bus service is considered satisfactory and should be maintained. The study recommends improving safety and comfort aspects to better meet passenger expectations.